2022
DOI: 10.1002/app.52814
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the depolymerization of polyethylene terephthalate in methanol

Abstract: With concern to sustainable development, it is necessary to establish a recycling process of polyethylene terephthalate (PET). Methanolysis of PET is promising for chemical recovery of PET and the products are mainly dimethyl terephthalate (DMT) and ethylene glycol (EG), but the conditions of state‐of‐art depolymerization are severe. Here, we synthesized ionic liquid [HO3S‐(CH2)3‐NEt3]Cl‐[ZnCl2]0.67 with Brönsted–Lewis di‐acid and used it to efficiently catalyze the methanolysis of PET (mmethanol:mPET about 4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…These signals are attributed to the BHET monomer, confirming that the main product of PET glycolysis with both catalysts (EtONa and MeONa), with both substrates (white and colored PET), and after multiple recycling runs is the monomer BHET. Furthermore, 13 C NMR of EG after recycling run R2 was also performed and is given in Figure 6S showing that NMR spectra after initial and recycling run R2 are similar, thereby conforming the filtrate after multiple glycolysis runs still constitute EG. The 13 C NMR results are also validated by HPLC and the chromatogram shown in Figure 7S indicates that the BHET monomer is the main product of PET glycolysis.…”
Section: Development and Optimization Of The Regression Model Experim...mentioning
confidence: 68%
See 3 more Smart Citations
“…These signals are attributed to the BHET monomer, confirming that the main product of PET glycolysis with both catalysts (EtONa and MeONa), with both substrates (white and colored PET), and after multiple recycling runs is the monomer BHET. Furthermore, 13 C NMR of EG after recycling run R2 was also performed and is given in Figure 6S showing that NMR spectra after initial and recycling run R2 are similar, thereby conforming the filtrate after multiple glycolysis runs still constitute EG. The 13 C NMR results are also validated by HPLC and the chromatogram shown in Figure 7S indicates that the BHET monomer is the main product of PET glycolysis.…”
Section: Development and Optimization Of The Regression Model Experim...mentioning
confidence: 68%
“…Furthermore, GR1 results show that both filtrates from colored PET waste were successfully recycled to get PET conversion up to 95%. The BHET crystals obtained under various conditions were subjected to 13 C NMR and signals at δ = 61, 67, 130, 134, and 166 ppm can be seen in Figure 5S. These signals are attributed to the BHET monomer, confirming that the main product of PET glycolysis with both catalysts (EtONa and MeONa), with both substrates (white and colored PET), and after multiple recycling runs is the monomer BHET.…”
Section: Development and Optimization Of The Regression Model Experim...mentioning
confidence: 77%
See 2 more Smart Citations
“…Additionally, they concluded that the ILs could be reused at least six to eight times without compromising the conversion rate [93] . Imidazolium‐based ILs have received the most extensive research of all the ILs for PET depolymerization as shown in Table 2 [94–121] . It is generally true that ILs containing metal ions are usually more catalytically efficient than their metal‐free counterparts; however, the existence of metal ions significantly reduces the purity of depolymerized products to a great extent.…”
Section: Depolymerisation Of Polyethylene Terephthalate (Pet or Pete)mentioning
confidence: 99%